Moving Towards a Language Nest: Stories and Insights from nḱmaplqs - Chambers, Natalie; Saddleman, Danielle (First Peoples Child & Family Review)

(untitled) (First Nations Child and Family Caring Society of Canada, 2020)
A language nest is an early language learning program for young children from infancy to five years of age. Language nests have the potential to reconnect young Indigenous children to their languages and cultures within the heart of their communities. The first author, a settler scholar and mother and grandmother of language nest children, shares some insights and experiences from her doctoral research with community members who have been involved in developing a language nest in nḱmaplqs, the Head of the Lake Okanagan Indian Band community in Vernon, British Columbia. The second author, an Okanagan Indian Band community member and Language and Culture Lead for her community, describes the language nest in the present day. We offer these stories and words of language nest development to encourage other Indigenous communities who are engaged in their own journeys of reclamation.